Postprandial Metabolism and Physical Activity in Asians: A Narrative Review - Nagayama, Chihiro; Burns, Stephen F.; Thackray, Alice E.; Stensel, David J.; Miyashita, Masashi (International Journal of Sports Medicine, 2021)
The widespread benefits of physical activity in enhancing health and lowering the risk of non-communicable chronic diseases are well established across populations globally. Nevertheless, the prevalence of several lifestyle-related chronic diseases, including cardiovascular disease, varies markedly across countries and ethnicities. Direct ethnic comparative studies on the health benefits of physical activity are sparse and evidence-based physical activity guidelines are not ethnicity-specific. Indeed, physical activity guidelines in some Asian countries were developed primarily based on data from Western populations even though the magnitude of potential benefit may not be the same among different ethnic groups. Unfavorable diurnal perturbations in postprandial triglycerides and glucose are risk factors for cardiovascular disease. This narrative review summarizes differences in these risk factors primarily between individuals of Asian and white European descent but also within different Asian groups. Moreover, the variable effects of physical activity on mitigating risk factors among these ethnic groups are highlighted along with the underlying metabolic and hormonal factors that potentially account for these differences. Future ethnic comparative studies should include investigations in understudied ethnic groups, such as those of East Asian origin, given that the effectiveness of physical activity for ameliorating cardiovascular disease varies even among Asian groups.
Keywords: postprandial triglyceridemia; postprandial glycemia; ethnicity; cardiovascular disease risk factors